PENGELOLAAN UNIT PRODUKSI BIDANG TATA BUSANA SMK MUHAMMADIYAH 5 SURAKARTA - Muhammad Adam Ilham Mizani; Ahmad Muhibbin; Achmad Fathoni (Media Bina Ilmiah, 2023)
This research is motivated by the author's interest in the activities of the production unit at SMK (Vocational High School) Muhammadiyah 5 Surakarta. SMK which is a non-profit institution that is able to manage a business, business or entrepreneur that is oriented towards home industry to improve students' skills in the field of fashion design. This study aims to determine the process or management of production units at SMK Muhammadiyah 5 Surakarta based on the stages of preparing production unit management. This research is descriptive qualitative. Data collection techniques use interviews, observations and literature studies. The results of this study show that the management of production units carried out by SMK Muhammadiyah 5 Surakarta uses a combination strategy of competency-based learning concepts and the production of goods and services. The production units owned include Mulia Batik Contemporary (MBC), Mulia Collection and clothing rentals and receive stitches. The resulting product also collaborates with several partners and uses digital-based marketing media and the use of social media such as Facebook, Instagram, marketplaces and business Whatsapp. The production unit also has a well-structured management such as the person in charge, marketing manager, digital marketing, finance manager, administration and is supported by human resources who are experts in their fields.